Green energy basic concepts and fundamentals - Li, Xianguo (Springer eBooks., 2011)
The Progress in Green Energy series explores the evolution of green energy systems for sustainable development and energy security. It focuses on the development of new technologies which enable the provision of energy with minimal negative effects on society and the environment. Progress in Green Energy is a monograph series, which aims to provide up-to-date information for researchers, engineers, and advanced students. The dominance or monopoly of a single energy system can provide a cumulative impact on a particular aspect of the environment, leading eventually to permanent damage or even catastrophe. Green Energy: Basic Concepts and Fundamentals addresses the need for diversity within energy systems. Although every energy system, including renewables and alternative fuels, has its own unique adverse impact, the impact need not be additive and cumulative. By using a diverse range of energy systems which exploit local energy resources, the energy need can be met without any negative impact beyond the tolerance limit of the environment. Additionally, energy diversity can withstand the fluctuations and disturbances in energy need, benefiting social and economic health in the process. Green Energy: Basic Concepts and Fundamentals focuses on the theme of energy diversity with local resources, and the integration and optimisation of conventional and alternative energy systems.